2002
DOI: 10.1124/jpet.302.1.304
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Efficacy with Parathyroid Hormone in Rats Was Not Entirely Beneficial with Long-Term Treatment

Abstract: We report the consequences of prolonged treatment with recombinant human parathyroid hormone (1-34) (PTH) in male and ovariectomized female rats with mature skeletons. Intact male and osteopenic, ovariectomized, female F-344 rats were evaluated after 1 year of treatment with 0, 8, or 40 g/kg/day s.c. PTH. Males and females were about 6 months of age at study initiation; females were ovariectomized (Ovx) for 5 weeks before initiation of PTH treatment. PTH did not affect the survival of either intact males or ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 42 publications
2
12
1
Order By: Relevance
“…However, recent studies have reported that longer treatment with this growth factor may not be practical, because it is a nonspecific mitogen with a potential for adverse side effects [17]. Furthermore, Sato et al reported that there seemed to be no advantages to extending PTH treatment to 12 months in rat bones compared with short-term treatments [26]. We believed that the regimen of lowdose PTH treatment in this study would be more suitable for clinical usage.…”
Section: Discussionmentioning
confidence: 90%
“…However, recent studies have reported that longer treatment with this growth factor may not be practical, because it is a nonspecific mitogen with a potential for adverse side effects [17]. Furthermore, Sato et al reported that there seemed to be no advantages to extending PTH treatment to 12 months in rat bones compared with short-term treatments [26]. We believed that the regimen of lowdose PTH treatment in this study would be more suitable for clinical usage.…”
Section: Discussionmentioning
confidence: 90%
“…Administration of PTH to animal models has been linked to the development of certain tumors as osteosarcoma (18). A more physiological administration such as the one we used, as the number of pulses delivered per hour in our patient is about the same of normal parathyroid glands (10,11), would probably be safer in this respect; moreover, the total dose given per day in our patient is similar to the one given in the study published by Winer, in which the patients were followed over 3 years without safety problems.…”
Section: Discussionmentioning
confidence: 99%
“…Animal toxicity studies have raised concerns regarding dose-dependent PTH effects on the bone. Long-term, supraphysiological doses of recombinant human PTH 1-34 (rhPTH), given to rats with normal functioning parathyroid glands, led to osteosarcomas in some experimental animals (19,20). This resulted in a warning against the use of PTH 1-34 in children.…”
mentioning
confidence: 97%